2021
DOI: 10.3389/fmicb.2021.778950
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Activation Enhanced by TRIM25 is Targeted by the NS1 Protein of 2009 Pandemic Influenza A Virus

Abstract: Nucleotide-binding domain and leucine-rich repeat-containing protein 3 (NLRP3) inflammasome-mediated interleukin-1 beta (IL-1β) production is one of the crucial responses in innate immunity upon infection with viruses including influenza A virus (IAV) and is modulated by both viral and host cellular proteins. Among host proteins involved, we identified tripartite motif-containing protein 25 (TRIM25) as a positive regulator of porcine NLRP3 inflammasome-mediated IL-1β production. TRIM25 achieved this function b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Interestingly, we detected for both, GAS mono-infection and superinfection an upregulation of Il1b, which suggests that the incapacity of co-infected macrophages to process and secrete IL-1β is due to a failure in the GAS-inducible activation of the NLRP3 inflammasome [86][87][88][89]. In fact, it was shown that different variants of IAV, including a 2009 pandemic strain, were capable of thwarting IL-1β maturation by interfering with NLRP3 inflammasome assembly [90][91][92], which is crucial for innate immune sensing and coordination [93]. An IAV-mediated nullification of IL-1β secretion would be of dramatic consequences during streptococcal superinfections.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, we detected for both, GAS mono-infection and superinfection an upregulation of Il1b, which suggests that the incapacity of co-infected macrophages to process and secrete IL-1β is due to a failure in the GAS-inducible activation of the NLRP3 inflammasome [86][87][88][89]. In fact, it was shown that different variants of IAV, including a 2009 pandemic strain, were capable of thwarting IL-1β maturation by interfering with NLRP3 inflammasome assembly [90][91][92], which is crucial for innate immune sensing and coordination [93]. An IAV-mediated nullification of IL-1β secretion would be of dramatic consequences during streptococcal superinfections.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, we detected an upregulation of Il1b for both GAS mono-infection and superinfection, which suggests that the incapacity of co-infected macrophages to process and secrete IL-1β is due to a failure in the GASinducible activation of the NLRP3 inflammasome [86][87][88][89]. In fact, it was shown that different variants of IAV, including a 2009 pandemic strain, were capable of thwarting IL-1β maturation by interfering with NLRP3 inflammasome assembly [90][91][92], which is crucial for innate immune sensing and coordination [93]. An IAV-mediated nullification of IL-1β secretion would be of dramatic consequences during streptococcal superinfections.…”
Section: Discussionmentioning
confidence: 85%
“…NS1 attenuates the association between pro-caspase-1 and ASC, followed by decreasing IL-1β signal transduction. Collectively, NS1 has an additional antagonistic effect on proinflammatory response to create a favorable environment for viral replication ( Figure 2E ) ( Park et al, 2021 ).…”
Section: Iav Escapes From Innate Immunementioning
confidence: 99%